Mental skills training for endurance sports - Carter, J. E.; Norman, J. L. (Endurance sports medicine, 2023)
Coaches often tell athletes to be mentally tough, especially when facing grueling endurance events. But how do athletes achieve mental toughness? They need to train their minds as well as their bodies. A sport psychologist and sports psychiatrist review research and provide tips for mental training in the following areas of endurance sport: motivation, goal setting, energy management, self-talk, concentration, imagery, routines, and mindfulness. We also include strategies for finding a healthy balance with exercise and discuss unique medication considerations for athletes.